Effect of in vitro simulated gastrointestinal digestion on the antioxidant activity of the red seaweed Porphyra dioica. (October 2020) - Pimentel, Filipa B.; Cermeño, Maria; Kleekayai, Thanyaporn; Harnedy, Pádraigín A.; FitzGerald, Richard J.; Alves, Rita C.; Oliveira, M. Beatriz P.P.
Graphical abstract: Highlights: Blades and protein isolates of P. dioica were digested. Simulated gastrointestinal digestion produced small bioactive peptides. Digested blades presented higher ORAC values compared to protein isolates. Protein isolates presented higher FRAP and ABTS + inhibition values. Simulated gastrointestinal digestion improved the antioxidant activity of samples. Abstract: Porphyra sp. is one of the most cultivated and commercially valuable species, recognized for its high protein content (up to 47% dry weight) and complete amino acids profile. Based on these characteristics, P. dioica produced in an integrated multitrophic aquaculture system was selected for this study. The aim was to evaluate the effect of in vitro simulated gastrointestinal digestion (SGID) on the antioxidant activity of the hydrolysates generated from dried blades and from the protein isolate (PI) extracted from them. The alkali extraction and isoelectric precipitation (pH 4.5) of P. dioica protein prior SGID allowed isolating/enriching protein, while direct SGID of blades allowed assessing the potential influence of other constituents of the sample on the bioactive properties. Overall, SGID promoted the release of smaller bioactive peptides and their in vitro antioxidant activity, which was assessed by different methods (DPPH and ABTS + scavenging capacity, ORAC and FRAP), was improved compared to the intact samples. Blades submitted to direct SGID presented significantly higher ORAC values compared to PI (2010 ± 136 vs 542 ± 21 µmol TE/g FDS, respectively). For the remaining assays, PI presented more potent antioxidant activity, especially FRAP (131 ± 2 vs 16 ± 1 µmol TE/g FDS) and ABTS + (1244 ± 157 vs 230 ± 15 µmol TE/g FDS). The results indicated that gastrointestinal digestion improved the antioxidant activity of P. dioica -derived hydrolysates, as they presented effective activity against different oxidative mechanisms, thus suggesting health-protecting effects.